Legal and regulatory aspects of improving the sanctions policy of Ukraine - K. L. Buhaichuk (Law and Safety)
The paper examines the legal nature of sanctions imposed by the UN Security Council and individual states to combat violations of international law. The UN Security Council sanctions have been identified as mainly economic restrictions and other coercive measures imposed for violations of major international human rights conventions and instruments.